Design of Web-Based Agricultural Product Marketing System in Toapaya Village - Rifaldi Herikson; Berta Erwin SLAM; Feri Irawan; Nolan Efranda (Universitas Putra Indonesia YPTK Padang, 2025)
Marketing agricultural products remains a major challenge for farmers in Toapaya Village, located in Bintan Regency. The selling prices received by farmers are often significantly lower than the market prices paid by end consumers. This is primarily due to the lengthy distribution chain and dependence on middlemen who take a large portion of the profits. Limited market access further weakens the farmers' position in setting prices and marketing their harvest independently. To address this issue, a web-based marketing system is proposed to facilitate direct transactions between farmers and customers, aiming to shorten the distribution chain and increase farmers' income. The system was developed using the Waterfall software development methodology to support a structured, user-oriented development process, while system modeling was carried out using UML to provide a detailed overview of the system flow. The research results indicate that the developed web-based marketing system can simplify the agricultural marketing process and expand market access. System evaluation will be conducted periodically through direct testing to collect feedback from users. Based on testing results, the system has been proven to enhance product accessibility and facilitate online transactions. Therefore, this marketing system is expected to contribute to economic growth, improve farmers' welfare, and serve as a form of digital transformation in the agricultural sector in Toapaya Village, Bintan Regency.